Impassioned Communication and Virtual Support Roles of Online Postings: The Case of Self-Harmers. (January 2019) - Davis, Sarah; Lewis, Christopher Alan
Although there is an emerging literature on online users support groups, limited research has focused on the online users support groups concerned with self-harm. This study reports the findings of inductive content analysis of self-harm online messages from one self-harm online users group. One hundred messages were examined. Categories were determined and inductive analysis revealed online self-harm postings showed two themes. The first theme was "impassioned communication, " 76% of the postings had this major theme. There were three subthemes included in this theme: being a "failure, " "people not understanding, " and "improvement." The second theme was "virtual support." Although presented as two separate themes, "impassioned communication" and "virtual support" are interrelated as some postings suggested the need for support with impassioned communication. These results support the established view that the Internet is the place where individuals can access emotional support or social integration, especially helpful for those who are, or feel, marginalized (e.g., those experiencing disenfranchised grief and self-harming). This study shows the usefulness of utilizing online message boards as a research tool for conducting research among populations that are difficult to access.